Understanding by Design (UBD) pada pembelajaran berbasis Problem Based Learning (PBL) berbantuan LKPD untuk meningkatkan kemampuan koneksi matematis siswa - Muhammad Ainun Niam; Sugiyanti; Dina Prasetyowati; Gunarto (Pascasarjana Universitas PGRI Semarang, 2024)
During the implementation of Field Experience Practices (PPL) at SMA Negeri 10 Semarang, researchers obtained data that students at the high school still experienced several obstacles and deficiencies in the learning process, understanding learning objectives, and relating the material to other things. Using a good learning model will help students connect concepts both in mathematics and in other fields. The aim of this research is to determine the increase in students' mathematical connection abilities in Understanding by Design (UbD) with problem-based learning (PBL) assisted by LKPD. This research uses classroom action research (PTK). The research procedure used consists of several stages, namely problem diagnosis, planning, action, observation, data analysis, and reflection. The sample in this research was class X-9 at SMAN 10 Semarang. The research results showed that in cycle I the average student learning outcome was 72.08 and classical completeness was only 44.44%. This is certainly very far from ideal. In cycle II the average learning result for class X-9 was 80.44 and classical completeness increased to 66.67%. Even though it has increased, it has not reached the ideal target, so treatment is needed in the third cycle. In cycle III the average learning outcome was 86.89 and classical completeness increased to 88.89%. This was said to be complete and successful. Thus, UbD with PBL assisted by LKPD can improve students' mathematical connection abilities in learning.